The Effect of E-Learning Platform Utilization and Digital Literacy on Elementary Students’ Critical Thinking Skills - Mohammad Junaidi; Onik Farida Ni’matullah; Dwi Fauzia Putra; Nawaji (South Sulawesi Education Development (SSED), 2026)
This study examines the effect of e-learning platform utilization and digital literacy on elementary students’ critical thinking skills. The study responds to the need for enhancing 21st-century learning by strengthening higher-order thinking skills. A quantitative survey method was employed at SDN Bugih 1 Pamekasan, involving 137 upper-grade elementary students (Grades IV–VI), and the data were analyzed using multiple linear regression to test both simultaneous and partial effects. The results show that e-learning platform utilization and digital literacy simultaneously have a significant positive effect on students’ critical thinking skills (R² = 0.524). Partially, both e-learning platform utilization and digital literacy also demonstrate significant positive effects, with e-learning showing a stronger contribution. Practically, these findings suggest that elementary teachers should move beyond using e-learning merely for material distribution by integrating inquiry-based online tasks and explicit digital literacy instruction to foster students’ critical thinking.